Milestone of the most used maximum power point tracking in solar harvesting system - Tole Sutikno; Arsyad Cahya Subrata; Mohd Hatta Jopri (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Solar harvesting system with photovoltaic (PV) is one of the most desirable renewable energy sources because of its prominent advantages. However, low efficiency due to fluctuating output power is a major problem for PV systems. A technique used to maximize power extraction known as maximum power point tracking (MPPT) has been proposed by various literature to deal with this problem. One of the most widely developed MPPT methods due to its ease of implementation is perturb and observe (P&O). Since the initial discovery of the principle, the P&O method has been extensively modified including the fixed step-size: step-size variables, partial shading, threshold module current, three-point-comparison, maximization of dynamic performance, minimization of dynamic performance, bandwidth of ???? − ???? curve, decoupling, observation of ????????, ????????, and ????????, datasheet parameters, curve fitting, voltage hold P&O, and observation of ???????? and ????????. This paper presents the development of the P&O method from the initial principle to the end as a reference source for readers. The hope is that a new easy and robust P&O method as a complement to the implementation of the MPPT technique is developed in the solar harvesting system.